2020
DOI: 10.1177/1753466620961648
|View full text |Cite
|
Sign up to set email alerts
|

Use of monoclonal antibodies for allergic bronchopulmonary aspergillosis in patients with asthma and cystic fibrosis: literature review

Abstract: Allergic bronchopulmonary aspergillosis (ABPA) is a hypersensitivity reaction (HR) mediated by antigens to Aspergillus fumigatus. It is estimated that 2–15% of patients with cystic fibrosis (CF) and between 1% and 5% of asthmatics develop ABPA, affecting approximately 4.8 million people worldwide. The goals of treatment are controlling inflammation, reducing the number of exacerbations and limiting the progression of lung damage. Systemic steroids are therefore used as the mainstay therapy, along with antifung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…In recent years, several studies and case reports have demonstrated the efficacy of anti-IgE antibodies and interleukin-5/interleukin-5 receptor-alpha (IL5/IL5-Rα) antibodies in the treatment of ABPA but was more beneficial for patients with asthma than for patients with CF [ [29] , [30] , [31] , [32] ]. Mepolizumab has been successfully used to treat patients with ABPA, showing improvement in FEV1, radiographic findings, decrease in total IgE levels, and quality of life without side effects and is considered a glucocorticoid-sparing agent [ [29] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. Altman et al reported that combination therapy with both omalizumab and mepolizumab improved ABPA, and together they may have a potential synergistic effect [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several studies and case reports have demonstrated the efficacy of anti-IgE antibodies and interleukin-5/interleukin-5 receptor-alpha (IL5/IL5-Rα) antibodies in the treatment of ABPA but was more beneficial for patients with asthma than for patients with CF [ [29] , [30] , [31] , [32] ]. Mepolizumab has been successfully used to treat patients with ABPA, showing improvement in FEV1, radiographic findings, decrease in total IgE levels, and quality of life without side effects and is considered a glucocorticoid-sparing agent [ [29] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. Altman et al reported that combination therapy with both omalizumab and mepolizumab improved ABPA, and together they may have a potential synergistic effect [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALI et al [ 41 ] and Mikura et al [ 42 ] reported a case of ABPA treated successfully with dupilumab. Two studies also evaluated dupilumab in 21 asthma patients treated for ABPA - IgE levels decreased by 35% from baseline and annual exacerbation rates decreased in 95% of patients [ 29 ]. Our patients with ABPA were treated with mepolizumab and dupilumab instead of omalizumab because of the high IgE levels they had.…”
Section: Discussionmentioning
confidence: 99%
“…The IgE effector functions are activated by its binding to Fc receptors FcɛRI and FcɛRII/CD23 [54]. Previous studies have shown that IgE antibodies triggered against A. fumigatus antigens can degranulate mast cells [55], and the biologics (Omalizumab) targeting IgE show variable effects in the clinic [56]. We observed serum IgE antibody titers to be elevated in female mice (p = 0.067) challenged with A. fumigatus, relative to naïve and male mice, at day 28 post-challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of specific clinically relevant disease endotypes has been greatly accelerated in respiratory medicine through the advent of systematic immunophenotyping studies [95, [139][140][141][142]. Given the current revolution in monoclonal antibody therapies in clinical medicine, with many agents now licensed for therapy of asthma and allergic rhinitis, repurposing of these monoclonals for allergic fungal airway diseases in particular, and better understanding of which may be more efficacious in this setting, is a current high priority [143,144]. We are already using omalizumab routinely for IgE depletion in allergic bronchopulmonary aspergillosis and severe asthma with fungal sensitization, with accumulating but mainly case series-based clinical data to support this approach [145][146][147].…”
Section: Personalized Medicine To Identify Clinically Relevant Endotypesmentioning
confidence: 99%